Modulation of polyketide biosynthetic pathway of the endophytic fungus, Anteaglonium sp. FL0768, by copper (II) and anacardic acid - Mafezoli, Jair; Xu, Ya-ming; Hilário, Felipe [UNESP]; Freidhof, Brandon; Espinosa-Artiles, Patricia; dos Santos, Lourdes C. [UNESP]; de Oliveira, Maria C.F.; Gunatilaka, A.A. Leslie (Elsevier, 2018)
In an attempt to explore the biosynthetic potential of endosymbiotic fungi, the secondary metabolite profiles of the endophytic fungus, Anteaglonium sp. FL0768, cultured under a variety of conditions were investigated. In potato dextrose broth (PDB) medium, Anteaglonium sp. FL0768 produced the heptaketides, herbaridine A (1), herbarin (2), 1-hydroxydehydroherbarin (3), scorpinone (4), and the methylated hexaketide 9S,11R-(+)-ascosalitoxin (5). Incorporation of commonly used epigenetic modifiers, 5-azacytidine and suberoylanilide hydroxamic acid, into the PDB culture medium of this fungus had no effect on its secondary metabolite profile. However, the histone acetyl transferase inhibitor, anacardic acid, slightly affected the metabolite profile affording scorpinone (4) as the major metabolite together with 1-hydroxydehydroherbarin (3) and a different methylated hexaketide, ascochitine (6). Intriguingly, incorporaion of Cu2+ into the PDB medium enhanced production of metabolites and drastically affected the biosynthetic pathway resulting in the production of pentaketide dimers, palmarumycin CE4 (7), palmarumycin CP4 (8), and palmarumycin CP1 (9), in addition to ascochitine (6). The structure of the new metabolite 7 was established with the help of spectroscopic data and by MnO2 oxidation to the known pentaketide dimer, palmarumycin CP3 (10). Biosynthetic pathways to some metabolites in Anteaglonium sp. FL0768 are presented and possible effects of AA and Cu2+ on these pathways are discussed.
Keywords: Anacardic acid; Anteaglonium; Copper (II); Endophytic fungus; Polyketide biosynthesis